El control interno y su relación con gestión administrativa del Hospital Apoyo Iquitos César Garayar García provincia de Maynas, 2018 - Gamarra Pinedo, Gina Scarlet (2021)
The present research has had the general objective of determining the relationship between internal control and administrative management of the Hospital Apoyo Iquitos César Garayar García, province of Maynas, 2018; opting to carry out a descriptive and correlational research, for which a sample of 7 administrative workers has been taken who were surveyed through a questionnaire of questions, which after analyzing the corresponding results, the work has managed to conclude that the The development of internal control in the hospital is regular, due to various deficiencies found in the system, such as establishing the responsibility and clear functions of the control team, as well as the lack of training for it, which often makes it difficult to development of specific control activities. On the other hand, it has been determined that the development of administrative management in the hospital is regular, given that deficiencies in the planning process have made it difficult to establish the essential guidelines for the development of the institution's activities. Finally, according to the inferential analysis, it is determined that there is a significant relationship between internal control and administrative management of the Hospital Apoyo Iquitos César Garayar García, province of Maynas, in 2018, which has been corroborated by the correlation coefficient of 0.850 and contrasted by a degree of significance of 0.000.